Occupation-focused intervention for in-patient mental health settings: Pilot study of effectiveness. (June 2020) - Lipskaya-Velikovsky, Lena; Krupa, Terry; Silvan-Kosovich, Ilana; Kotler, Moshe
Abstract: Purpose: Participation in meaningful occupation is associated with recovery in serious mental illnesses, however, few evidence-based, occupation-focused interventions for hospital settings exist. This study investigated the effectiveness of "Occupational Connections" (OC), a manualized, short-term, group intervention, addressing issues in daily-life occupations' participation and functioning of people with serious mental illness as early as during hospitalization. Methods: Thirty-three inpatients with schizophrenia completed single-blind, pre-post study procedures (up to 10 weeks) in two groups: OC group intervention and open leisure activity group (control condition), in addition to treatment as usual. They were assessed for occupation and participation dimensions, perceptions of services as recovery-oriented, comprehensive cognitive functioning and schizophrenia symptoms. The sampling was convenience with sequential group allocation. Results: Improvements were found in the study group in the following measurements: intention to participate in daily activities (t(15) = -2.62, p < .05), participation diversity (t(15) = -2.11, p < .05), experience the recovery orientation of the service (t(15) = -3.15, p < .01), functional capacity (t(15) = -3.44, p < .01), cognitive abilities of language understanding, memory and shifting (−4.5<t(15)<3.3, p < .05), and schizophrenia symptoms (positive, negative and general: 8.47<t(15)<9.12, p < .01). The control group has improved on attention (t(16) = -2.89, p < .05), visual-motor organization (t(16) = 2.14, p < .05) and schizophrenia symptoms (4.4<t(16)<6.6, p < .01) only. Conclusions: The study provides initial evidence for the effectiveness of OC. The results suggest that interventions with a focus on personal, meaningful daily life occupations such as the OC, may be a useful tool contributing to a positive experience of the in-patient staying and successful community reintegration after acute psychiatric hospitalization. Highlights: Participation in meaningful occupation of personal choice has been limited in psychiatric inpatient settings, while it is an important component of the recovery in serious mental illnesses. Today, little evidence exists on interventions oriented toward promotion of everyday life occupations and recovery needs for hospital settings. Occupation-focused intervention, such as OC, may be useful for positive influence on the occupational parameters, experience of hospital staying, cognition and symptoms of inpatients diagnosed with schizophrenia.